Residential units market in the provincial capitals of Poland in 2019-2022 - Aneta Dorota Zaremba (Rozprawy Społeczne)
Abstract The purpose of this article is to reposition the situation in the secondary market for residential units in the provincial capitals of Poland in 2019-2021. The study shows a large spatial variation in the number of transactions made, unit prices and rental rates for residential units.